Analysis of the Effects of Inflation, Unemployment, Minimum Wages, and Economic Growth on Labor Absorption in East Java - Indri Nauwalalkhoir; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2025)
The problem of employment in Indonesia is increasingly complex with the covid-19 pandemic. One of the affected areas is East Java Province, where it was recorded that formal labor absorption fluctuated from 2020 to 2023. Meanwhile, the Labor Force Participation Rate has increased from year to year. The increase in the labor force is faster than the growth of employment opportunities so that it will cause poverty, crime, and adverse socio-economic phenomena. This study aims to determine the effect of inflation (X1), unemployment (X2), minimum wages (X3) and economic growth (X4) on labor absorption (Y). The data used includes 38 regencies / cities in East Java Province from 2020 to 2023. The research data analysis method uses panel data regression analysis. The results of the regression state that the variables of inflation, unemployment, minimum wage and economic growth simultaneously affect labor absorption. Partially, the variables of inflation, minimum wage and economic growth affect labor absorption. Meanwhile, unemployment variable partially has no effect on labor absorption.